2016
DOI: 10.1097/moh.0000000000000254
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic Notch signaling in T-cell and B-cell lymphoproliferative disorders

Abstract: Purpose of review Highlight recent discoveries about Notch activation and its oncogenic functions in lymphoid malignancies, and discuss the therapeutic potential of Notch inhibition. Recent findings NOTCH mutations arise in a broad spectrum of lymphoid malignancies and are increasingly scrutinized as putative therapeutic targets. In T cell acute lymphoblastic leukemia (T-ALL), NOTCH1 mutations affect the extracellular negative regulatory region and lead to constitutive Notch activation, although mutated rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 89 publications
0
40
0
Order By: Relevance
“…In B-ALL, chemotherapy upregulates CXCR4 expression in surviving leukemic blasts and accounts for the therapeutic resistance [103]. Recently, Notch signaling has been shown as a common feature in ALL, in particular in more than 60% of T-ALL [104][105][106]. Both hyperactive Notch1 and Notch3 enhances CXCR4 expression in thymus-derived .…”
Section: Cxcl12/cxcr4 Axis In Hematological Tumors: a Crucial Hub Formentioning
confidence: 99%
See 1 more Smart Citation
“…In B-ALL, chemotherapy upregulates CXCR4 expression in surviving leukemic blasts and accounts for the therapeutic resistance [103]. Recently, Notch signaling has been shown as a common feature in ALL, in particular in more than 60% of T-ALL [104][105][106]. Both hyperactive Notch1 and Notch3 enhances CXCR4 expression in thymus-derived .…”
Section: Cxcl12/cxcr4 Axis In Hematological Tumors: a Crucial Hub Formentioning
confidence: 99%
“…In B-ALL, chemotherapy upregulates CXCR4 expression in surviving leukemic blasts and accounts for the therapeutic resistance [102]. Recently, Notch signaling has been shown as a common feature in ALL, in particular in more than 60% of T-ALL [103][104][105]. Both hyperactive Notch1 and Notch3 enhances CXCR4 expression in thymus-derived and in BM-derived T-cells in T-ALL [106,107], and CXCR4 silencing inhibited the expansion of leukemic cells [106] through disruption of the Notch/CXCR4 partnership [102].…”
Section: Cxcl12/cxcr4 Axis In Hematological Tumors: a Crucial Hub Formentioning
confidence: 99%
“…It was reported that >60% of T-ALL cases present with abnormal activation of the Notch1 signaling pathway, indicating that Notch1 might be the most common oncogene in T-ALL (55). Mutations of Notch1 occur mainly in the heterodimeric domain region and the proline, glutamine, serine, and threonine domain (56,57). Activating mutations of Notch1 gene result in sustained expression of genes regulating T cell differentiation, including Hes family bHLH transcription factor 1 and CD25, changing the expression balance of c-Myc and p27 (58-60), upregulating the NF-κB signaling pathway (5), enhancing the expression of the anti-apoptotic X-linked inhibitor of apoptosis protein associated with ubiquitination and degradation, and activating the PKB/Akt/mTOR signaling pathway-mediated inhibition of p53 (61).…”
Section: Role Of the Fbw7 Gene In Common Hematological Tumorsmentioning
confidence: 99%
“…The best known oncogenic feature linked to Notch pathway is probably the abovementioned NOTCH1 activating translocation present in T‐ALL . Further, truncations of the PEST domain of NOTCH1 and NOTCH2 lead to increased half‐life of NICD, found in some B cell malignancies …”
Section: Introductionmentioning
confidence: 99%